Questioning mandatory sentencing efficiency: A case study of persistent felony offender rapists in Kentucky - Kunselman, Julie C. (American journal of criminal justice, 2002)
This policy analysis explores the incapacitative efficiency of Kentucky’s career criminal statute in averting the recidivism of offenders convicted of rape. The study utilizes a 1985 cohort of Kentucky persistent felony offenders with at least one rape conviction (n = 62) and tracks recidivism rates up to fifteen years later. The results question the efficiency of mandatory sentencing. In general, mandatory minimum sentences (where offenders are not eligible for statutory good time or parole) kept these offenders incarcerated beyond the time necessary to avert future crimes.